Colonic Manometry in Pediatric Patients with Spina Bifida: Results from a Retrospective Cohort Study - Albert Yuh Chyuan Shan; Barry Duel; Timothy Phillips; Paula Buchanan; Leonel Rodriguez; Dhiren Patel (Children, 2025)
Background/Objectives: Patients with spina bifida (SB) commonly experience neurogenic bowel dysfunction, characterized by defecation-related symptoms. While anorectal dysfunction and slow transit constipation (STC) have been implicated, the role of colonic motility in SB remains unclear. This study aimed to evaluate colonic motility in SB patients with refractory bowel dysfunction. Methods: This retrospective cohort study included SB patients who failed the repeated optimization of a bowel regimen including stimulant laxatives and subsequently underwent anorectal manometry (ARM), colonic transit time (CTT) studies, or colonic manometry (CM). Diagnostic findings were analyzed alongside treatment outcomes. Results: A total of 13 patients with myelomeningocele were included; one declined further treatment, and 12 underwent treatment optimization, with four achieving bowel continence. Of the five patients who proceeded with advanced motility testing, two had abnormal ARM findings, one of three had abnormal CTT results, and all five had normal CM findings. Conclusions: These findings suggest that anorectal dysfunction or STC may play a larger role in refractory bowel symptoms, while colonic motility appears to be preserved, and this highlights the importance of maximizing conservative therapies, particularly with stimulant laxatives, before pursuing invasive tests or surgical interventions for bowel dysfunction in this population.